Gambaran Kadar Hemoglobin dan Karbon Monoksida pada Pedagang Sate - Yuvita; Asti Mulasari, Surahma; Suryani, Dyah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Background: Satay smoke contains a pollutant called carbon monoxide (CO). Carbon monoxide (CO) is a colorless and odorless substance, but contains toxins that can adversely affect human health, especially will affect hemoglobin levels in the body. This systematic review of literature review aims to describe hemoglobin and carbon monoxide (CO) levels in satay traders. This research is a literature review, so the data base used in searching this article uses secondary sources derived from google scholar and sage publications with the keywords "hemoglobin, carbon monoxide, Carbon Monoxide (CO)" which have been done by previous researchers both domestically and abroad. From a total of 300 articles, finally obtained 5 articles relevant to the title made by the researcher. From these 5 selected articles, data were obtained that the substances contained in satay smoke have an influence on hemoglobin levels in the body. The longer the exposure to smoke, the high risk of hemoglobin levels in the body of the satay seller will decrease. This is certainly not good for the health of the body. Therefore, satay sellers are advised to use PPE (Personal Protective Equipment) in the form of masks to minimize the absorption of substances contained in satay smoke. Carbon monoxide (CO) can affect hemoglobin levels in the body of satay traders